Biomass composite with exogenous organic acid addition supports the growth of sweet sorghum (Sorghum bicolor ‘Dochna’) by reducing salinity and increasing nutrient levels in coastal saline–alkaline soil - Yang, Ruixue; Sun, Zhengguo; Liu, Xinbao; Long, Xiaohua; Gao, Limin; Shen, Yixin (Frontiers in Plant Science, 2023)
In coastal saline lands, organic matter is scarce and saline stress is high. Exploring the promotion effect of intervention with organic acid from biological materials on soil improvement and thus forage output and determining the related mechanism are beneficial to the potential cultivation and resourceful, high-value utilization of coastal mudflats as back-up arable land. Three exogenous organic acids [humic acid (H), fulvic acid (F), and citric acid (C)] were combined with four kinds of biomass materials [cottonseed hull (CH), cow manure (CM), grass charcoal (GC), and pine needle (PN)] and applied to about 0.3% of medium-salt mudflat soil. The salinity and nutrient dynamics of the soil and the growth and physiological differences of sweet sorghum at the seedling, elongation, and heading stages were observed under different treatments to screen for efficient combinations and analyze the intrinsic causes and influencing mechanisms. Results showed that the soil salinity, nutrient dynamics, and forage grass biological yield during sweet sorghum cultivation in saline soils differed significantly (p < 0.05) depending on the type of organic acid–biomass composite applied. Citric acid–pine needle composite substantially reduced the soil salinity and increased the soil nutrient content at the seedling stage and improved the root vigor and photosynthesis of sweet sorghum by increasing its stress tolerance, allowing plant morphological restructuring for a high biological yield. The improvement effect of fulvic acid–pine needle or fulvic acid–cow manure composite was manifested at the elongation and heading stages. Based on these results, citric acid–pine needle composite promoted the growth of saline sweet sorghum seedlings, and the effect of fulvic acid–pine needle composite lasted until the middle and late stages.